Grading of Engineering Institutes - Singh, B. B.; Chaurasia, S. P. (Journal of Engineering Education Transformations, 2000)
The present paper deals with a new approach of grading the engineering institutes by using quantifiable indicators to measure their performance standards. Whilst measuring the performance of the Institutes, students' input level/out put level service conditions of the employees, leadership, people involvement and working environment have also been taken into consideration; along with the infra-structural facilities and teaching faculty of the institutes.